Prevalence of Cercarial Dermatitis among Paddy-Field Workers in Central Areas of Mazandaran Province - B Rahimi-Esboei; M Fakhar; A Ghorbani; M Pour Haji Baqer; AS Paqeh; P Shahnasi; M Rezaei (Medical Laboratory Journal, 2013)
Abstract